(untitled) (Journal of University of Babylon for Engineering Sciences, 2019)
Combined flow over and under structure may solve the problem of the deposit of suspension materials in channels. Semi-cylindrical shape reduces the curvature of streamlines which reflected on its performance. To study how this shape performs, experimental and simulation has been done. The laboratory models were of four different diameters and four different gate openings. The same physical structures have been modeled in commercial software, FLOW-3D®, by employing RNG k- ε turbulence model. The verification has been based on measured flow profile and discharge. Simulation outputs indicate that a separation zone located at a distance from the structure became farther when the diameter and gate opening decreases, also the separation portions and their thickness are related to the incoming discharge. The location height of separation zone tends to be lower when there is an increase in flow discharge and it is located at half the total depth when two flow portions are equal. The weir flow in this system shows a better performance than traditional weir by at least 33%, while the gate out flow is less than free flow of the same total head by 70% to 90%. Within the limitation of this work, two mathematical models for predicting discharge coefficient have been proposed for the weir and gate respectively, moreover a model for predicting relative discharge of weir to gate, and one mathematical model for the dimensionless total discharge.